Poems from the Edge - Wilson, Lyn Hatherly (LiNQ (Literature in North Queensland), 2016)
Contemporary Australian Poets edited by Hale and Iremonger, The Blue Cloud of Crying by Peter Boyle, The Book of Possibilities by Jill Jones and 100 Elegies for Modernity by John Leonard are reviewed by Lyn Hatherly Wilson.